(untitled) (Revista Cocar, 2023)
No contexto do protagonismo da pessoa com deficiência de territórios do campo, este artigo apresenta a trajetória e o protagonismo de uma jovem com deficiência física que reside no campo e tem por mote sua arte de desenhar e criar modelos ou projetos da área da moda. Orienta-se por uma abordagem qualitativa com análise que cruza dados e autores especializados na área. Conclui-se que há discreto protagonismo de pessoas com deficiência, no entanto, como estilista de território do campo, há apenas a apresentada neste artigo; e, a falta de estrutura e oportunidade nos municípios de pequeno porte e comunidades do campo inviabilizam o acesso e permanência na educação e educação profissional. Palavras-chave: Pessoa com deficiência; Protagonismo; Acesso e permanência. Abstract In the context of the protagonism of people with disabilities in rural territories, this article presents the trajectory and protagonism of a young woman with a physical disability who lives in the countryside and whose motive is her art of designing and creating models or projects in the fashion area. It is guided by a qualitative approach with analysis that crosses data and authors specialized in the area. It is concluded that there is a discreet role for people with disabilities, however, as a stylist in rural areas there is only one presented in this article and the lack of structure and opportunities in small municipalities and rural communities make access and permanence in education unfeasible and education professional. Key words: Person with disability; Protagonism; Access and permanence.